COMPARISON OF 2-DE PROTEOME MAPS OF WHEAT, RYE AND AMARANTH - Zdenka Gálová (Journal of Microbiology, Biotechnology and Food Sciences, 2015)
The protein maps of wheat (Triticum aestivum L.), cv. Brea; rye (Secale cereale L.), cv. Oklon and amaranth (Amaranthus sp.) cv. Plaisman were obtained by performing 2-DE over a broad pH range (pH 3-11NL) to obtain total protein profiles. Focussing on the gluten fraction, as it is the major trigger for Celiac disease, proteins were separated with a basic pI over a narrow pH range of pH 6-11. Putative identifications of proteins were determined using current literature. The overall spot pattern from wheat over pH 6-11was identified as gamma-gliadins (~ pI 8-10, Mrs 28 - 30, 000 Da), alpha/beta-gliadins (~pI 6.5-7.5, Mrs 25 - 35, 000 Da) and gluten proteins (pI 6-10, Mrs 35 - 60, 000 Da.). The rye had a higher number of abundant groups visible over a broad range (~ 6-200,000 Da, pI 4-9). Comparison of rye to wheat protein maps showed that each cereal had completely different spot patterns in the LMW region of the gels (<14,000 Da), but similarities were observed in the HMW and MMW regions. This is especially evident in the pH 6-11 gels. Amaranth has many proteins focussed between pH 3-11. Fewer proteins were observed for the pH 6-11 gel, especially in the HMW weight region of the gel. This is due to the fact that the pseudocereals are a botanically different species compared to cereal grasses, and even if they are rich in protein, unfavourable fractions are not present or are only available in small amounts.